Epigenetics of schizophrenia: A focus on the DNA methylation mechanism and expression of DISC1 gene - A.Talib, Norlelawati; Ku Zaifah, Norsidah; Abdullah, Kartini; Abd. Rahim, Nour El Huda (2018)
Epigenetic DNA methylation and Schizophrenia